Scenario analysis for energy banking between Nepal & India from Nepali perspective - Puri, Bijay; Mishra, Arbind Kumar (Journal of Innovations in Engineering Education, 2021)
Government of Nepal has agreed with India on energy banking with aim to enhance the energy security of respective national grids. The general concept of this banking is that the surplus energy available in Nepal during the wet months is absorbed by the power system of India and Nepal will retrieve the much needed banked energy during dry months. However, major challenge to quantify the energy being transacted and bring this into feat is, the hydro generation projects being not completed in scheduled time and uncertainties in the domestic consumption. Even the authentic reports from different governmental agencies contradict each other in estimating future internal electrical energy consumption pattern. The lack of rigid national grid‐supply is a key constraint to enhance the domestic demand and seems to be the crucial factor for import/export location & respective line power flow selection. This paper illustrates the prospective scenario analysis for monthly surplus – deficit energy during the period of fiscal year 2077/78 BS to 2084/85 BS from Nepalese prospective. The scenarios viz. commissioning of upcoming generating projects in accordance to Power Purchase Agreement (PPA) concluded date as well as with trending delays are taken into account. The consumption sector with normal energy growth and with intervention like heavy penetration of electric vehicle and electric induction cooking, are considered during the analysis. The modeling of planned INPS and simulation is performed in ETAP. The cross – border transmission line flows and avenues as well as operating behavior of planned INPS are also analyzed.